AUGMENTED REALITY PENGENALAN OBJEK WISATA TAMAN MUMBUL SANGEH BERBASIS ANDROID - Kadek Agus Wirawan; I Gede Harsemadi; Ni Kadek Sukerti (IIB Darmajaya, 2021)
Mumbul Park Tourism Object is a tourist attraction located in Sangeh Village, Abiasemal District, Badung Regency. In Mumbul Park there are two temples named Pura Luhur Mumbul (Puru Ulun Siwi) and Pura Ulun Mumbul. In addition to the temple in the Mumbul Sangeh Park Tourism Object, there is a pengelukatan called Pancoran Solas and there is a pond (lake) with thousands of fish. The Mumbul Park Tourism Object has its own charm for tourists, but the lack of information regarding the Mumbul Sangeh Park Tourism Object makes not many people know about the tourist area. Therefore, we need an introduction media regarding the object of the Mumbul Sangeh park which is more modern with Android based Augmented Reality media. This application contains direct information about the history of the Mumbul Park Tourism Object, Pancoran Solas 3D Penglukatan Object, Ulun Danu Temple and the Queen Niang Sakti Statue, Videos and Photos of the introduction of Mumbul Park. The method used in this research is the MDLC (Multimedia Development Life Cycle) method and the C # programming language. The making of this application uses Unity3D, CorelDraw and Adobe Illustrator as the interface designer, Adobe Premiere to edit the introduction video. Based on the results of tests carried out using two testing methods, namely blackbox testing and questionnaires. This application is distributed via Google Drive.. Keywords—Mumbul Sangeh Park, Pancoran Solas, Ulun Danu Temple, Ratu Niang Sakti Statue, Augmented Reality, Android